Realization of Vindication Claim on Immovable Property and Some Counterclaims - Zarnadze, Eka; Chalidze, Tamar (Journal of Law, 2023)
The article is devoted to the problems of realizing the Vindication claim as a means of protecting the right to property in the Georgian legal order, in the form of researching the procedural and material legal features of this kind of lawsuits and presenting recommendations to overcome the delay in their consideration.